Edukasi Gerakan Masyarakat Hidup Sehat (GERMAS) untuk Percepatan Penurunan Stunting sebagai Praktik Kampung Keluarga Berkualitas: (Studi Kasus Di Desa Kota Karang Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi) - Guspianto, Guspianto; Asparian, Asparian; Kusmawan, David; Pramudiani, Dessy; Nurlinawati, Nurlinawati (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
Indonesia was still facing the problem of malnutrition, namely Stunting as a disorder of child growth and development characterized by short stature for their age which impacts the quality of human resources. The causes of stunting are multifactorial and mostly originate from family factors, so efforts to reduce stunting must focus on family empowerment, one of which is the Healthy Living Community Movement (GERMAS). This Community Service (PkM) activity aims to improve clean and healthy living behavior (PHBS) in the community, namely mothers of toddlers in Kota Karang Village, Kumpeh Ulu District, Muaro Jambi Regency as part of the implementation of good practices of the Quality Family Village (KB Village). PkM activities were carried out 6 (six) times by providing GERMAS education on PHBS including physical activity, healthy nutritious food, smoking behavior and alcohol consumption, health checks, environmental cleanliness, personal hygiene, and use of family toilets. The analysis results obtained an increase in the average PHBS behavior score of mothers of toddlers before and after the intervention. The highest average value difference is the behavior of healthy nutritious food (5.76) followed by family toilets (4.17), personal hygiene (2.52), environmental cleanliness (1.35), smoking and alcohol consumption behavior (0.94), regular health checks = 0.77 and physical activity = 0.76. These results indicate the influence of GERMAS education intervention on the PHBS behavior of mothers of toddlers